Food and feeding habits of freshwater cypnnid, Amblypharyngodon mola (Ham.) - Pishka, Ravi Shankar; Swamy, B Rama; Devi, P Indira (Indian Journal of Fisheries, 2011)
Amblypharyngodon mola (Ham.), aherbivorous bottm feeder, feeds on algae,diatoms and higher aquatic plants. Differentfood items in relation to size, seasonal variationand intensity of feeding were investigatedin this fish.